Correlates of self-reported dietary cruciferous vegetable intake and urinary isothiocyanate from two cohorts in China. Issue 7 (7th August 2014) - Vogtmann, Emily; Yang, Gong; Li, Hong-Lan; Wang, Jing; Han, Li-Hua; Wu, Qi-Jun; Xie, Li; Cai, Quiyin; Li, Guo-Liang; Waterbor, John W; Levitan, Emily B; Zhang, Bin; et al.
Abstract: Objective: To assess correlations between cruciferous vegetable intake and urinary isothiocyanate (ITC) level, in addition to glutathione S -transferase ( GST ) genotypes and other individual factors. Design: The study included cohort participants whose urinary ITC levels had been previously ascertained. Urinary ITC was assessed using HPLC. Usual dietary intake of cruciferous vegetables was assessed using a validated FFQ and total dietary ITC intake was calculated. Recent cruciferous vegetable intake was determined. GST genotypes were assessed using duplex real-time quantitative PCR assays. Spearman correlations were calculated between the covariates and urinary ITC levels and linear regression analyses were used to calculate the mean urinary ITC excretion according to GST genotype. Setting: Urban city in China. Subjects: The study included 3589 women and 1015 men from the Shanghai Women's and Men's Health Studies. Results: Median urinary ITC level was 1·61 nmol/mg creatinine. Self-reported usual cruciferous vegetable intake was weakly correlated with urinary ITC level ( r s =0·1149; P <0·0001), while self-reported recent intake was more strongly correlated with urinary ITC ( r s =0·2591; P <0·0001). Overall, the GST genotypes were not associated with urinary ITC level, but significant differences according to genotype were observed among current smokers and participants who provided an afternoon urine sample. Other factors, including previous gastrectomy or gastritis, were also related to urinary ITC level. Conclusions: The study suggests that urinary secretion of ITC may provide additional information on cruciferous vegetable intake and that GST genotypes are related to urinary ITC level only in some subgroups.